The clinical indexes and immunological status of HIV/AIDS patients undergoing different highly active antiretroviral treatments - Wan, Xinrui; Li, Mingyu; Wang, Hongye; Zhang, Ruixian; Lu, Xiaoning; Song, Yu; He, Chenglu; Zhang, Renning; Sun, Ming; Chen, Hongying; Li, Ya (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThis study aims to investigate the differences of clinical indices in HIV patients between three different first-line antiretroviral treatment strategies in Yunnan Province, China. Furthermore, the hematologic system, liver function, kidney function, blood lipid levels of HIV patients and its association with CD4+ count, CD8+ count, CD4/CD8 ratio and antiretroviral treatment were also assessed.MethodsThis retrospective cohort study included 81 participants who underwent highly active antiretroviral treatment from September 2009 to September 2019. Baseline sociodemographic and clinical characteristics were collected from each study participant. Routine blood tests, liver and renal function, lipid levels as well as lymphocyte subset counts were measured and recorded for evaluation before and 3, 6, 9, and 12 months after the treatment. Paired t-test was used to compare clinical indices changes after antiretroviral treatment. Univariate linear regression was performed to determine the association between clinical indices and CD4+ count, CD8+ count, CD4/CD8 ratio and antiretroviral treatment.ResultThere were no statistical differences in baseline demographic and clinical characteristics in either treatment group. Compared with the initiation of HARRT treatment, the CD4+ count(p < 0.001), CD4/CD8 ratio(p < 0.001) and PLT(p < 0.001) were increased in the three treatment groups. The TC(p < 0.01) and TG(p < 0.05) were increased in 3TC+AZT+EFV group after treatment. The ALT(p < 0.05), AST(p < 0.01) were decreased in 3TC+EFV+TDF group after treatment. The study indicated statistical differences in CD4+ count (p < 0.001), CD8+ count (p < 0.001), and CD4/CD8 ratio (p < 0.001) in the three treatment cohorts. Furthermore, a strong positive correlation was observed between WBC (p < 0.001), platelet (p < 0.001), Hb (p < 0.001), and CD4+ count in the three treatment cohorts. Moreover, ALT and AST were negatively associated with CD4+ count in the 3TC + AZT + EFV group. Whereas WBC were positively correlated with CD8+ count in the three treatment methods. In addition, platelet and TG were positively correlated with CD8+ count in the 3TC + EFV + TDF. The study also indicated that TC was positively associated with CD8+ count in the 3TC + AZT + NVP group. Furthermore, WBC was negatively related to CD4/CD8 ratio in the 3TC + EFV + TDF group. The platelet level analysis revealed a positive, while TG indicated a negative association with CD4/CD8 ratio in the 3TC + AZT + NVP group. Moreover, ALT and AST were negatively correlated with the CD4/CD8 ratio in the 3TC + AZT + EFV and 3TC + AZT + NVP groups.ConclusionThe results showed that HIV/AIDS patients treated with different first-line antiretroviral treatment strategies had different hematopoietic, liver, renal and immune system functions. Furthermore, some clinical indicators such as WBC, PLT, TC, TG, and ALT could predict the CD4+ count, CD8+ count, CD4/CD8 ratio levels and recuperation of HIV/AIDS patients, therefore, should be monitored by clinicians.